Diffusional-thermal instability in strained diffusion flames with unequal Lewis numbers - Kim, JS; Lee, SR (TAYLOR & FRANCIS LTD, 1999)
Diffusional-thermal instability is analysed for near-extinction counterflow diffusion flames to examine the instability characteristics of strained diffusion flamelets in turbulent flames, with the additional intention of providing a guideline to future experimental investigations; Attention is focused on the linear stability of the instability patterns appearing in the unstrained direction of two-dimensional counterflow diffusion flames, which is treated by the near-equilibrium regime of activation-energy asymptotics with Lewis numbers close to unity. The effects of unequal Lewis numbers for fuel and oxidizer are also taken into account by introducing an effective Lewis number. The resulting formulation describing linear stability of the harmonically decomposed disturbances turns out to be identical to the formulation derived previously for equal fuel and oxidizer Lewis numbers. For effective Lewis numbers less than unity, cellular instability is predicted for the entire range of the equivalence ratio, and the threshold Lewis number maintains a value slightly less than unity. On the other hand, for effective Lewis numbers sufficiently greater than unity, two types of oscillatory instabilities are found. As the effective Lewis number increases from unity, a travelling instability is first encountered for a range of finite wavelengths, and a pulsating instability emerges immediately above the travelling instability. These two types of oscillatory instabilities are predicted only for equivalence ratios sufficiently greater than unity because the threshold Lewis numbers for these instabilities are found to be infinity at unity equivalence ratio. For large values of the equivalence ratio, which is typical of most hydrocarbon flames, oscillatory instabilities are predicted only for flames burning extremely heavy hydrocarbon fuels pi for dames heavily diluted by light inert gases.
Keywords: ASYMPTOTIC STRUCTURE; LINEAR-ANALYSIS; LAMINAR FLAMES; STABILITY